Happy Gilmore [videorecording (DVD)] - Dugan, Dennis; Sandler, Adam; McDonald, Christopher, 1955-; Bowen, Julie; Weathers, Carl (Universal, 2004)
Although Happy dreams of becoming a professional hockey player, he discovers that his hockey slap shot translates to an astonishing 400 yard tee shot. So when his grandmother loses her home to the IRS, Happy decides to earn the house back by joining the pro golf tour, bringing his ferocious temper and outlandish antics to the well-tended fairways. Before long, Happy is a media sensation, attracting crowds and news cameras wherever he goes. But Happy's bitter rival has his own plans for the golf superstar, resulting in a riotous, laugh-filled confrontation on the links.